Inorganic nitrate attenuates cardiac dysfunction: roles for xanthine oxidoreductase and nitric oxide. (6th October 2021) - Gee, Lorna C.; Massimo, Gianmichele; Lau, Clement; Primus, Christopher; Fernandes, Daniel; Chen, Jianmin; Rathod, Krishnaraj S.; Hamers, Alexander J. P.; Filomena, Federica; Nuredini, Gani; Ibrahim, Abdiwahab Shidane; Khambata, Rayomand S.; et al.
Abstract : Background and purpose: NO is a vasodilator and independent modulator of cardiac remodelling. Commonly, in cardiac disease (e.g., heart failure), endothelial dysfunction (synonymous with NO deficiency) has been implicated in increased BP, cardiac hypertrophy and fibrosis. Currently, no effective therapies replacing NO have succeeded in the clinic. Inorganic nitrate (NO3 − ), through chemical reduction to nitrite and then to NO, exerts potent BP lowering, but whether it might be useful in treating undesirable cardiac remodelling is not known. Experimental approach: We analysed demographics in a nested age‐ and sex‐matched case–control study of hypertensive patients with or without left ventricular hypertrophy (NCT03088514) and assessed the effects of dietary nitrate in mouse models of cardiac dysfunction. Key results: Lower plasma nitrite concentrations and vascular dysfunction accompanied cardiac hypertrophy and fibrosis in patients. In mouse models of cardiac remodelling, restoration of circulating nitrite levels using dietary nitrate improved endothelial dysfunction through targeting the xanthine oxidoreductase‐driven increase in levels of H2 O2 and superoxide, and decreased cardiac fibrosis through NO‐mediated block of SMAD phosphorylation leading to improvements in cardiac structure and function. Conclusions and implications: Dietary nitrate offers easily translatable therapeutic options for delivery of NO and thereby treatment of cardiac dysfunction.